Validity and Reliability the Questionnaires of Teachers` Self-Efficacy and Teaching Competency in School Drug Education - Ahmad Jazimin Jusoh; Suzaily Wahab; Raja Jamilah Raja Yusof (International Journal of Pedagogy and Learning Community (IJPLC), 2025)
This study aimed to assess the validity and reliability of two questionnaires used in drug education in Malaysian secondary schools: Teachers' Self-Efficacy (TSE) and Teaching Competency (TC). The questionnaires, originally in English, were translated into Malay for participants, who included 43 secondary school teachers and 9 educational experts from three public universities in Malaysia. The findings showed that items with an acceptance rate above 70% supported the content and construct validity of the instruments. However, experts recommended excluding two TC items for being repetitive and unrelated. The reliability test revealed a Cronbach's alpha of .973 for the TSE and .964 for the TC, indicating both questionnaires' trustworthiness. The study concluded that the TSE and TC are valid and reliable tools for research in drug education. The researchers emphasized the importance of these factors in teachers' drug education effectiveness and recommended that government policy support efforts to enhance teachers' self-efficacy and teaching competency in this area.